2014
DOI: 10.1007/s10113-014-0626-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis in land change science: methodological patterns, challenges, and guidelines

Abstract: Global and regional economic and environmental changes are increasingly influencing local land-use, livelihoods, and ecosystems. At the same time, cumulative local land changes are driving global and regional changes in biodiversity and the environment. To understand the causes and consequences of these changes, land change science (LCS) draws on a wide array synthetic and meta-study techniques to generate global and regional knowledge from local case studies of land change. Here, we review the characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
99
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(104 citation statements)
references
References 59 publications
3
99
0
2
Order By: Relevance
“…By designing the study for comparison from the beginning, we wanted to fill the gap between the single case studies and the meta-analyses, and address some of the challenges of syntheses in land change science, as described by Magliocca et al (2015). Moreover, we feel that combining information on LULC changes as shown in maps and remote sensing data and landscape changes as perceived by the local population to be a mixed-method approach which deserves further application in that it considers and takes advantage of the complementarity and the specific strength and limitations of the various source types (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By designing the study for comparison from the beginning, we wanted to fill the gap between the single case studies and the meta-analyses, and address some of the challenges of syntheses in land change science, as described by Magliocca et al (2015). Moreover, we feel that combining information on LULC changes as shown in maps and remote sensing data and landscape changes as perceived by the local population to be a mixed-method approach which deserves further application in that it considers and takes advantage of the complementarity and the specific strength and limitations of the various source types (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…constellations of prerequisites which, if combined with a specific set of potential driving forces, result in a somewhat predictable change. Meta-analyses are limited by the diversity of approaches applied and the case studies included (Magliocca et al 2015). In addition, the distribution of the case-studies found in meta-analyses hardly reflects the diversity of the system under study in a meaningful way, as they were not planned and conducted with the aim of representing a larger area but with specific aims and objectives regarding a particular location or landscape.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper's methodological goal is to examine the case study-based documentation of the linkages of agrobiodiversity and related resource use to global change consisting of livelihood diversification (Section 3) and ecological systems with an emphasis on soil-plant interactions and biodiversity (Section 4). We employ the methodology of meta-analysis to research these linkages [74][75][76]. First, we conduct an analysis of the interactions of recent livelihood diversification with agrobiodiversity use and the related management of soils, water, and uncultivated biodiversity (Section 3).…”
mentioning
confidence: 99%
“…First, we conduct an analysis of the interactions of recent livelihood diversification with agrobiodiversity use and the related management of soils, water, and uncultivated biodiversity (Section 3). We place emphasis on migration and on-farm cash cropping as two common forms of Meta-analysis has become significant in research on global change and social-ecological systems in order to synthesize expanded fields of study as well as to advance new understandings and hypotheses [74][75][76]. Design of this study's meta-analyses draws also on our extensive personal experience in field-based research on the linkages of biodiversity and soil and water management to livelihoods and livelihood changes.…”
mentioning
confidence: 99%